Work Stretch Properties for the Scheduling of Continuous Operations Under Alternative Labor Policies - Lowerre, James M. (Management Science, 1977)
For a seven-day's-a-week operation in which N employees are needed on each weekday and n on each weekend day, with N at least as large as n, the work stretch is developed for each of several different rest policies. The work stretch is the number of consecutive work days between rest days. Additionally, work force size formulas are developed for policies not previously covered in the literature.